(untitled) (Research, Society and Development, 2023)
The gastroschisis is a congenital anomaly that affects the closure of the abdominal wall, leaving the intestine exteriorized. It is seen that this morphological alteration has been showing a higher incidence, due to social, environmental and genetics factors. Therefore, the use of ultrasonography in prenatal care is increasingly important in today’s society, because throught it that changes in fetal formation can be identified and the case can be conducted in the best possible way. This work is a descriptive and qualitative case report. The purpose of this study is to describe the diagnosis of a casa of paraumbilical gastroschisis to the right of the umbilical stupm, identified since the first trimester, in which the fetus showed signs suggestive of malformation. Patient and fetus were closely monitored with post natal confirmation, with birth at 35 weeks and five days. Due to prematurity, the newborn was referred to the Neonatal Intensive Care Unit (ICU).